Drug allergies in primary care practice in Romania: a questionnaire - based survey - Leru, Polliana Mihaela (BioMed Central, 2014)
INTRODUCTION: Recent data from literature have shown many difficulties in managing allergic diseases in primary care in most countries and a consequently clear need for standardized educational programmes. Drug allergies represent an important medical issue for general practitioners (GPs) in Romania, though no national data about incidence, severity and management exist.The aim of our study was to evaluate epidemiological aspects of drug allergies in primary care practice in Bucharest, especially the diagnostic and therapeutic attitudes of family doctors and their need for education and training in this field of pathology. FINDINGS: A questionnaire with 21specific questions was addressed to 800 family doctors from Bucharest, either directly or via internet, with a response rate of 31,87%. The answers showed a significant interest of GPs in drug allergies, which are considered an increasing pathology. Almost half of the responders had never attended any form of education in allergology and 96% expressed a clear interest to participate in specialized educational programmes. We have noticed an underestimation of the severity of drug allergy, a surprisingly high percentage of allergy skin tests or blood tests recommended by GPs without specialist advice, and persistant confidence in alternative medicine. CONCLUSIONS: We concluded that the attitude towards and the competence regarding drug allergies of GPs in this study, as well as their collaboration with allergists, are not standardized and updated according to current guidelines. Further educational programs for GPs in drug allergies, based on standardized guidelines and national epidemiological studies for evaluation of drug allergy-related morbidity and mortality are needed.